ANALISIS SUMBER DAYA MANUSIA TERHADAP KETERANDALAN PELAPORAN KEUANGAN PADA PEMERINTAHAN PROVINSI SULAWESI UTARA - Hullah, Abdurahman Rigel; Pontoh, Winston (ACCOUNTABILITY, 2017)
Researcher interested in conducting a study with "Human Resourcesâ€™s Effect Against Financial Reportingâ€™s Reliability In North Sulawesi Provincial Governmentâ€ as the title, because many were relying on information in the financial reports who were published by the regional government as a basis for decision making, therefore in North Sulawesi provincial governmentâ€™s financial reporting a reliable Human Resources is necessary. Issues in this study is: does human resources affect the reliability of financial reporting in North Sulawesi provincial government? While the goal is to determine the effect of human resources to the reliability of financial reporting. The analytical method used is simple linear regression analysis and tested using classic assumption test. As for the processing of research data SPSS version 24 were used. The test results showed that Human Resources partially have effects on North Sulawesi Provincial Governmentâ€™s Financial Reporting Reliability. Keywords : Human resources, reliability, financial reporting.